Effect of Teams Games Tournament Model on Students’ Science Achievement - Dinda Aprilya; Abd Hakim Laenggeng; Lita Iriani (Equator Science Journal, 2025)
This study aimed to enhance students’ learning outcomes through the application of the Team Games Tournament (TGT) cooperative learning model. The research followed a Classroom Action Research (CAR) design and was carried out in two cycles, each consisting of four stages: planning, implementation, observation, and reflection. The participants were 36 Grade XI Science 5 students at SMAN 1 Palu during the even semester of the 2024/2025 academic year. Learning outcomes were evaluated using the class average scores from the final evaluation sheets, supported by the percentage of students who achieved mastery learning. Data were collected through Google Forms and analyzed using a five-point Criterion-Referenced Assessment (CRA) scale. The findings revealed an improvement in learning achievement from Cycle I to Cycle II. In Cycle I, the average student score was 73.87, categorized as moderate, whereas in Cycle II it increased to 85.21, categorized as high. Additionally, the mastery learning percentage rose from 45% in Cycle I to 71.3% in Cycle II. These results indicate that the implementation of the TGT cooperative learning model effectively enhances students’ learning outcomes in Biology.